(Bio)manufactured Solutions for Treatment of Bone Defects with an Emphasis on US‐FDA Regulatory Science Perspective. Issue 4 (5th April 2022) - Ghelich, Pejman; Kazemzadeh-Narbat, Mehdi; Hassani Najafabadi, Alireza; Samandari, Mohamadmahdi; Memić, Adnan; Tamayol, Ali
Abstract : Biomanufacturing In article number 2100073, Mehdi Kazemzadeh‐Narbat, Ali Tamayol, and co‐workers emphasize on the fabrication strategies for bone tissue engineering and their United States Food and Drug Administration regulatory perspective. Bone biology and materials for engineering bone grafts are discussed. (Bio)manufacturing approaches are critically reviewed. Subsequently, a road map for United States Food and Drug Administration conformance is provided.